MOUNTAINEERS OF THE NORTH CAUCASUS ON THE CORONATIONS OF RUSSIAN EMPERORS (XIX - THE BEGINNING OF THE XX CENTURY) - Arsanukaeva, M S (History, Archeology and Ethnography of the Caucasus, 2015)
The article shows how in the 19th century the representatives of the mountaineers from the North Caucasus participated in the coronations of Russian emperors, it deals with the body of deputies, their provision and encouragement. Beginning with Nicholas I, all the emperors at such ceremonies were escorted by the personal guard in which representatives of many Caucasian peoples served. The courtesy to the deputies and possibility to communicate with the leaders of the Russian state became one of the means of successful adaptation of mountaineers and created the conditions for dialogue with the authorities.